Future improvements on performance of an EU landfill directive driven municipal solid waste management for a city in England. (1st February 2020) - Wang, Dan; Tang, Yu-Ting; Long, Gavin; Higgitt, David; He, Jun; Robinson, Darren
Highlights: EU directives improved the performance of MSW management in Nottingham. More materials need to be recycled to meet the EU, national and local targets. To separate the food waste will be critical to the improvement of MSW management. Abstract: Sustainable municipal solid waste (MSW) management is regarded as one of the key elements for achieving urban sustainability via mitigating global climate change, recycling resources and recovering energy. Landfill is considered as the least preferable disposal method and the EU Landfill Directive (ELD) announced in 1999 requires member countries to reduce the volume of landfilled biodegradable materials. The enforcement of ELD initiated the evolution of MSW management system UK. This study depicted and assessed the transition and performance of MSW management after the millennium in Nottingham via materials flow analysis (MFA), as well as appropriately selected indicators based on the concept of waste management hierarchy and targets set in waste management regulations. We observed improvements in waste reduction, material recycling, energy recovery, and landfill prevention. During the period 2001/02 to 2016/17, annual waste generation reduced from 463 kg/Ca to 361 kg/Ca, the recycling and composting share increased from 4.6% to 44.4%, and the landfill share reduced from 54.7% to 7.3%. These signs of progress are believed to be driven by the ELD and the associated policies and waste management targets established at the national and local levels. An alternative scenario with food waste and textile separation at source and utilizing anaerobic digestion to treat separately collected organic waste is proposed at the end of this paper to fulfil the high targets set by local government and we further suggest that the recycling share may be improved by educating and supporting the public on waste separation at the sources.